India : Energy-Efficient Street Lighting--Implementation and Financing Solutions - World Bank (Washington, DC, 2015)
There has been a clear need for energy-efficient (EE) technologies that can be applicable in the municipal street lighting sector. The objective of this manual is to support the preparation and implementation of street lighting projects in India, using performance contracting and other public private partnership-based delivery approaches. This manual draws upon global best practices, including practices that have been tried and presented within India and South Asia; and draws from their failures and successes to document the major lessons learned. The manual provides a brief overall background of EE in India, the kind of barriers faced in the implementation of EE projects, and the kind of prevalent policy environment for EE in the country. The manual is divided into eight sections. Section one provides an overview of EE street lighting, its components, Indian standards for outdoor lighting, the key lamp technologies, and the potential for intelligent street lighting systems. Section two highlights the financial models for implementation of street lighting projects. Section three describes the essentials of undertaking a detailed energy audit to develop robust baselines. Section four focuses on procurement and contracting. Section five describes methodologies for developing monitoring and verification (M and V) protocols for EE Street lighting projects. Section six brings together the useful tools and matrices in implementation of street lighting projects. Section seven lists the key stakeholders involved in India in such projects and their potential role. Section eight provides details on international and Indian case studies on implementing EE in street lighting and key lessons from these case examples.